Peningkatan Kemampuan Guru Dalam Pengelolaan Proses Pembelajaran Melalui Pelaksanaan Supervisi Akademik - Belman Panjaitan (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This study aims to determine the implementation and improvement of teachers' abilities in managing PBM through the implementation of academic supervision with Classroom Visition Technique at SMAN 2 Tarutung Semester 1 Academic Year 2019. The research subjects were 8 teachers. Data collection techniques using observation and documentation study. The validity of the data used triangulation techniques. Data analysis using qualitative analysis. The results showed that in the initial conditions there were no teachers who were able to organize the management of the teaching and learning process properly as evidenced by the low results of the average score obtained by the teachers, namely 49.75 in the low category, in cycle I there were 4 or 50 teachers. , 00% by obtaining a classical average value of 69.88 and included in the sufficient criteria and in the last cycle became a teacher or 100%, as evidenced by the acquisition of a value of 89.38 in the criteria for good grades.